Service quality and customer satisfaction of private banks - Crispín Aranda, Jhony Luis (2020)
Objective. To determine the influence of service quality and customer satisfaction clients in private banks in the city of Huánuco, 2019. Methods. It was a quantitative research and its design was non-experimental. Data was collected through the survey technique and a questionnaire to evaluate the quality of service and customer satisfaction. Population comprised 32,000 clients who were served, on average, monthly and the sample consisted of 380 clients. Rho Spearman was used as statistical proof. This was done using the SPSS software (version 24.0). Results. It was evidenced that the service quality influences the satisfaction of the clients in private banks of Huánuco, existing a considerable direct correlation (rs = 0.785, Sig. = 0.000). Conclusion. The research concluded that there is a significant relationship between service quality and customer satisfaction in private banks in the city of Huánuco -2019.